Associations Between Loss of ARID1A Expression and Clinicopathologic and Genetic Variables in T1 Early Colorectal Cancer. Issue 4 (2nd July 2019) - Kishida, Yoshihiro; Oishi, Takuma; Sugino, Takashi; Shiomi, Akio; Urakami, Kenichi; Kusuhara, Masatoshi; Yamaguchi, Ken; Kitagawa, Yuko; Ono, Hiroyuki
Abstract: Objectives: To evaluate the relationships between adenine-thymine-rich interactive domain 1A (ARID1A) expression and the clinicopathologic features in T1 colorectal cancer (CRC) and to investigate whether the presence of ARID1A protein is related to genetic changes. Methods: We retrospectively studied 219 surgically resected T1 CRCs. ARID1A expression was assessed by immunohistochemical methods, and the correlation between ARID1A expression and clinicopathologic features was evaluated. The relationship between ARID1A expression and 409 cancer-related gene mutations was also evaluated using next-generation sequencing (NGS). Results: Immunohistochemical staining indicated negative ARID1A expression in 4.6%. Loss of ARID1A expression was significantly associated with younger age, lymphatic invasion, and lymph node metastasis (LNM). NGS showed that PKHD1, RNF213, and MSH6 mutations were more frequent in ARID1A-negative tumors, whereas KRAS mutations were more common in ARID1A-positive tumors. Conclusions: In T1 CRC, negative ARID1A expression was correlated with early onset, lymphatic invasion, and LNM. Mutations in some cancer-related genes were possibly related with ARID1A expression.